CRIMINAL PUNISHMENT FOR CRIMINALS WHO DELIBERATELY INCITE MINORS TO HAVE SEXUAL INTERCOURSE (CASE STUDY CASE NO. 215/PID.SUS/2024/PN SBR) - Rohmatulloh, Muhammad Zidan; Lennas , Putri Ayu; Rahadatul Aisy, Nanda Syazwina; Suherman, Yoga; Fathurohman, Dadan Taufik (Jurnal Abdisci, 2025)
Abstract: Background. In the case of criminal acts involving minors as victims, criminal sanctions have a more complex aspect, as they focus not only on punishment for the perpetrator, but also on the protection of vulnerable victims. The act of sexual intercourse of minors is included in the category of moral crimes, where behaviors, actions, or conversations related to norms of decency must be maintained and protected by law. Aims. This aims to realize order and morality in community life. This study aims to outline the rules of criminal law and the sanctions imposed on perpetrators of criminal acts who deliberately persuade minors to have sexual relations, both with themselves and others. Methods. This study uses a normative juridical approach by examining the theory, concept, laws, and regulations of the Source District Court Decision No. 215/Pid.Sus/2024/PN Sbr. Result. The results of this study conclude that criminal acts involving children as victims are a category of special criminal acts, which are regulated in special laws and regulations regarding child protection, criminal provisions are also applied to every individual who deliberately using deception, a series of lies, or persuading a child to have intercourse with himself or with others, and criminal sanctions against the perpetrators of criminal acts in case No. 215/Pid.Sus/2024/PN Sbr. based on the provisions on child protection have been fulfilled, where the Panel of Judges sentenced the defendant to imprisonment, with a prison sentence of 10 (ten) years and a fine of Rp. 500,000,000.00 (five hundred million rupiah). Conclusion. Criminal acts involving children as victims are categorical special criminal acts, which are regulated in special laws and regulations governing child protection, such as Law No. 17 of 2016, a double amendment to Law No. 23 of 2002 on Child Protection. Implementation. Criminal penalties are imposed on individuals who intentionally use force, a series of lies, or persuade a child to have sexual intercourse with themselves or with another person